Burn injury in epileptics: The trend and risk factors in the middle belt of Ghana. Issue 3 (July 2018) - Agbenorku, Pius; Adamu Bukari, Abdul-Rahman; Effah, Angelina Tima; Agbenorku, Manolo; Asare, Nana Yaa Odamea; Bayuo, Jonathan
Highlights: Burns admission among epileptics is considerably low. Females are at higher risk of burn accidents. 81% of the epileptic burns are scalds. Epileptics on admission at BICU spent more days than other burn patients. Abstract: Background: Burns is one of the injuries associated with epilepsy. Unfortunately, epileptics are afflicted with severe burns when they come in contact with burn substances, due to loss of consciousness while seizing. Objective: This study is designed to inform stakeholders about the incidence, outcomes and trends of burn accidents among epileptics predominantly in the middle belt of Ghana. Methods: A retrospective study of all burn cases (May 2009 to April 2016) resulting from seizures reporting at the Komfo Anokye Teaching Hospital was undertaken. Patient demographics, burns aetiology, total burnt surface area and length of admission were obtained from stored electronic data (Excel) of the Burns Intensive Care Unit (BICU). History related to burn injury were obtained from patients' folders. Data was statistically analysed using Excel version 2013. Results: Epileptics formed 3.1% (n = 21) of the total BICU admissions and average annual incidence of 2.6 persons per year. Majority of the patients were females (71.42%). Age group 11–30 years formed the preponderance of our patients (n = 18, 85.7%). Only one 0–10 years old and no ≥50 years old patient was admitted. Scalds was the major aetiology (81.0%, n = 17). Ninety-five percent of the patients suffered moderate to major burns. Mean TBSA = 19.1%. Average days on admission was 69.1 days. Mortality rate was 9.5%. Conclusion: Though burns among epileptics is comparatively low in the middle belt of Ghana, it is important that stakeholders continually educate the public on epilepsy and burns prevention.